Drinking water quality, exposure and health risk assessment for the school-going children at school time in the southwest coastal of Bangladesh - Md. Aminur Rahman (IWA Publishing, 2021)
Scarcity of safe drinking water in the coastal regions throughout the world has long been recognized due to hydrological vulnerability and natural disaster, which is severe in developing countries like Bangladesh. This study focuses on trace metal(loid)s contamination and their associated health risks for primary school children from the consumption of tubewell water at school time in the vulnerable southwest coastal region of Bangladesh. The average content of electrical conductivity (EC), turbidity, chloride, total dissolved solids (TDS), hardness, iron (Fe), and manganese (Mn) were 1,983.6 ± 1,434.6 μS cm−1, 10.46 ± 10.3 NTU, 676.3 ± 648.1, 1,089.1 ± 788.6, 560.6 ± 326.6, 2.18 ± 1.99, and 0.19 ± 0.36 mg L−1, respectively, which exceeded their respective health-based guideline values. The concentrations of arsenic (As), cadmium (Cd), lead (Pb), and zinc (Zn) were lower than the World Health Organization provisional guideline values. Spearman's correlation analysis revealed that the EC of groundwater is dependent on TDS, chlorides, and other cations contributing to hardness, while turbidity results from the Fe content in groundwater. The hazard quotients (HQs) of As, Fe, Mn, and Zn intake were lower than unity for both boys and girls, indicating no non-carcinogenic risks to the children. However, cancer risks (CRs) from As exposure through drinking water were 1.5 and 1.8 times higher than the provisional safe value of 10−4 for boys and girls, indicating a lifetime cancer risk to the school-going children. Therefore, prompt and effective monitoring is a crying need to ensure water's continuous usability for drinking purposes in the study area. Highlights The EC, chloride, TDS, and hardness of drinking water were beyond the guidelines.; Iron and manganese content were higher than the WHO guideline values.; pH has a negative correlation with all the other variables.; Although arsenic content was low, it poses a lifetime cancer risk to the children.;